1999
DOI: 10.1046/j.1471-4159.1999.0722059.x
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Enhances Iron Uptake and Expression of Neurofibrillary Tangle Protein in Neuroblastoma Cells

Abstract: Aluminum (AI) and iron (Fe) have been implicated as playing a toxic role in the pathologic lesions of Alzheimer's disease. In the following report we describe the uptake and toxicity of Al, the effect of Al on Fe uptake, and the expression of neurofibrillary tangle (NFT) protein in murine neuroblastoma cells (Neuro 2A). Significant cell Al uptake and inhibition of cell growth were seen in Neuro 2A cells at 24, 48, 72, and 96 h after plating in medium containing Al transferrin (AI-Tf) and Al citrate. Al-loaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The neurotoxic effect of Al has also been related to the morphological and biochemical characteristics of beta-amyloid and neurofibrillary tangles and has often been related to oxidative stress [50]. The evidence in mouse neuroblastoma cells indicated that Al enhance Fe uptake and the expression of neurofibrillary tangle protein [51]. Apparently, this evidence supported that Al may still be a toxicant playing a pivotal role in the causation of uremic patients with dementia.…”
Section: Discussionmentioning
confidence: 96%
“…The neurotoxic effect of Al has also been related to the morphological and biochemical characteristics of beta-amyloid and neurofibrillary tangles and has often been related to oxidative stress [50]. The evidence in mouse neuroblastoma cells indicated that Al enhance Fe uptake and the expression of neurofibrillary tangle protein [51]. Apparently, this evidence supported that Al may still be a toxicant playing a pivotal role in the causation of uremic patients with dementia.…”
Section: Discussionmentioning
confidence: 96%
“…Taking together the present and previous findings, it is conceivable that fucoidan-binding Al may move into the S-phase nucleus. A number of studies of a variety of cultured cell lines have shown that Al loading resulted in abnormal Fe accumulation and compartmentalization [31][32][33]. Co-localization of Al and Fe has been found in hepatocytes of dialysis patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase Activity Assay The PC12 cells (1ϫ10 7 ) were washed twice with CMF-PBS and then suspended in an icecold 50-mM potassium phosphate buffer (pH 7.5). To prevent the non-specific cleavage of proteins, cell lysis was performed by two cycles of freezing and thawing at 4°C.…”
Section: )mentioning
confidence: 99%
“…6) Several lines of research that use cultured cells and the aluminum-maltolate complex (Al(maltol) 3 ), which is a membrane permeable, lipophilic complex of Al, also showed that the exposure of cells such as the Neuro-2a murine neuroblastoma cells, 7) human NT2 neuroblastoma cells, 8) and PC12 cells 9,10) to the Al complex results in a decrease in cell viability via the apoptotic cell death pathway. Recently, we have reported that the treatment of PC12 cells with Al(maltol) 3 causes a decrease in the levels of the intracellular reduced glutathione depending on the amount of Al(maltol) 3 accumulated in the cells.…”
mentioning
confidence: 99%